ASPP2 suppresses invasion and TGF-β1-induced epithelial–mesenchymal transition by inhibiting Smad7 degradation mediated by E3 ubiquitin ligase ITCH in gastric cancer. (10th July 2017) - Gen, Yasuyuki; Yasui, Kohichiroh; Kitaichi, Tomoko; Iwai, Naoto; Terasaki, Kei; Dohi, Osamu; Hashimoto, Hikaru; Fukui, Hayato; Inada, Yutaka; Fukui, Akifumi; Jo, Masayasu; Moriguchi, Michihisa; et al.
Abstract: ASPP2 regulates cell polarity and cell–cell adhesion by binding to, and co-localizing with PAR3 at tight junctions. Here we show a novel role of ASPP2 in suppressing gastric cancer (GC) invasiveness. Immunoprecipitation and immunofluorescence analyses showed that ASPP2 promoted the recruitment of PAR3 to cell–cell junctions in GC cells. Diminished expression of ASPP2 and loss of junctional PAR3 localization were significantly associated with diffuse-type histology, deeper invasion depth, positive peritoneal dissemination and worse prognosis in primary GC. ASPP2 suppressed migration and invasion of GC cells in vitro and peritoneal dissemination of GC cells in vivo in a mouse model. ASPP2 suppressed epithelial–mesenchymal transition (EMT) induced by TGF-β1-Smad2/3 signaling in GC cells through suppression of the degradation of Smad7, a negative regulator of TGF-β1-Smad2/3 signaling, by interacting with the E3 ubiquitin ligase ITCH. In conclusion, ASPP2 suppresses invasion, peritoneal dissemination and TGF-β1-induced EMT by inhibiting Smad7 degradation mediated by ITCH. Highlights: ASPP2 suppresses invasion and TGF-β1-induced EMT in gastric cancer (GC) cells. ASPP2 expression was diminished frequently in diffuse-type GC. ASPP2 promotes the recruitment of PAR3 to cell–cell junctions in GC cells. ASPP2 suppresses TGF-β1-Smad2/3 signaling via elevation of Smad7 in GC cells. ASPP2 reduces ubiquitin-dependent degradation of Smad7 by interacting with ITCH.